2019
DOI: 10.3389/fmolb.2019.00029
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ligand Binding to G-Protein Coupled Receptors Using Multiscale Simulations

Abstract: Human G-protein coupled receptors (GPCRs) convey a wide variety of extracellular signals inside the cell and they are one of the main targets for pharmaceutical intervention. Rational drug design requires structural information on these receptors; however, the number of experimental structures is scarce. This gap can be filled by computational models, based on homology modeling and docking techniques. Nonetheless, the low sequence identity across GPCRs and the chemical diversity of their ligands may limit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 105 publications
(204 reference statements)
0
24
0
Order By: Relevance
“…In humans, TAS2Rs are a family of 25 type A G protein coupled receptors (GPCRs) (versus 35 TAS2Rs in rats and mice) according to their structure and binding site location (Di Pizio et al, 2016, 2019; Alfonso-Prieto et al, 2019). Although TAS2Rs have been found in many species, in each species their genes are not highly conserved in terms of sequence.…”
Section: Structure and Function Of Tas2rsmentioning
confidence: 99%
“…In humans, TAS2Rs are a family of 25 type A G protein coupled receptors (GPCRs) (versus 35 TAS2Rs in rats and mice) according to their structure and binding site location (Di Pizio et al, 2016, 2019; Alfonso-Prieto et al, 2019). Although TAS2Rs have been found in many species, in each species their genes are not highly conserved in terms of sequence.…”
Section: Structure and Function Of Tas2rsmentioning
confidence: 99%
“…Studies have suggested that human G protein-coupled receptors (GPCRs) including the formyl peptide receptors (FPRs), free fatty acid receptors (FFAR) and mast-cell specific GPCR (MRGPRX2) can recognize bacterial signaling peptides and are involved in host defense against pathogens [3][4][5][6]. Recent studies have shown that the 25 bitter taste receptors (T2Rs) in humans which form the third largest GPCR group, act as important sensors for the bacterial quorum sensing molecules (QSMs) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, whole-cell signal transduction in the tongue is silenced through the downregulation of the G-protein coupled receptors (GPCRs), class A/1 (rhodopsine-like receptors), and G alpha (i) signaling events. GPCRs (including rhodopsin class A) are pleiotropic receptors detecting a large range of extracellular signals (from photons to hormones and neurotransmitters), consequently triggering numerous intracellular transduction cascades that reflect on many physiological functions ( 39 ). It also regulates the activity of the G alpha (i), whose classical signaling mechanism consists of cAMP-dependent pathway inhibition through the inhibition of adenylate cyclase ( 40 ).…”
Section: Discussionmentioning
confidence: 99%